2014
DOI: 10.1002/pen.23879
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and properties of perfluorosulfonic acid polymer/perfluorocarboxylic acid polymer blend membranes

Abstract: A melt-extruded method has been used to prepare blend membranes of Perfluorosulfonic Acid Polymer (PFSA) and Perfluorocarboxylic Acid Polymer (PFCA) with different combination ratios. Fourier Transform Infrared (FT-IR) and X-ray Diffraction (XRD) analyses have showed that the chemical structure and crystallization behaviour of both polymers remained unchanged in the blend membrane, and the crystallinity has been increased for the blend membrane with a higher weight fraction of PFCA. According to the results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Wang et al [92] studied the effect of blend layers with different ratios of PFSA to PFCA on the performance of composite membranes. The distribution morphology of the blend membrane has a great influence on its ion transport performance and water absorption capacity.…”
Section: Advanced Membrane Designmentioning
confidence: 99%
“…Wang et al [92] studied the effect of blend layers with different ratios of PFSA to PFCA on the performance of composite membranes. The distribution morphology of the blend membrane has a great influence on its ion transport performance and water absorption capacity.…”
Section: Advanced Membrane Designmentioning
confidence: 99%
“…However, Buddhi et al [ 23 ] reported that the electrolysis efficiency of the NaCl solution was better with trace amounts of Mg 2+ in it, demonstrating the complexity of the ion effects under different electrolyte environments. In fact, the impurity ions were usually limited to very low concentrations to ensure the H 2 /Cl 2 production efficiency for either water electrolysis or saturated NaCl solution electrolysis [ 24 , 25 , 26 ]. In detail, the concentration of SO 4 2− should be no higher than 0.05 mol/L for the purpose of 30% NaOH solution production and much lower for 42% or 50% NaOH solution production [ 27 ] in the chlor-alkali industry.…”
Section: Introductionmentioning
confidence: 99%
“…TEM and scanning transmission electron microscopy (STEM) has been widely used to directly image the morphology and distributions of acid groups in dry thin films of sulfonated ionomers. [ 45‐52 ] However, the analyses of 2‐D projection were limited by overlapped features in the thin film, (thickness is much larger than acid group size), and electron beam damage. [ 37,53 ] Low‐dose imaging and STEM tomography 3D reconstructions enabled the quantitative characterization of the location and size distribution of sulfur‐rich clusters in a free‐standing dry polystyrene sulfonate‐ b ‐polymethylbutylene (PSS‐ b ‐PMB) thin film.…”
Section: Introductionmentioning
confidence: 99%